Fenomena Culture Shock Pada Mahasiswa Perantauan Tingkat 1 Universitas Negeri Padang - Puji Gusri Handayani; Verlanda Yuca (Jurnal Konseling dan Pendidikan)
This study aims to describe culture shock of students outside and inside Sumatra and examine the differences in student culture shock based on gender and region of origin. The study population was 2018 level 1 / class students at Padang State University who migrated to Padang from outside and inside West Sumatra with a sample of 300 students selected by simple random sampling technique. The instrument used is "Inventory Culture Shock" (ICS) with a reliability of 0.74. The findings of the study show that culture shock of students from outside West Sumatra is classified as medium and originating from within West Sumatra is relatively low. Then, there was no difference in culture shock between students from outside and in West Sumatra.